What is An Emerging Market? - Mody, Ashoka (International Monetary Fund, 2004)
As developing economies become richer, they seek to contract with the global economy in increasingly complex ways. Dealing with that complexity often implies the need to renegotiate contracts. However, such recontracting is viewed with concern, particularly by market participants. At the same time, iron-clad commitments to abstain from recontracting are untenable. Sovereign debt experts have long dealt with this dilemma. This paper argues that the acute trade-off between commitment and flexibility is not unique to sovereign debt. Instead, it is the defining characteristic of an emerging market. Examples of World Bank guarantees on behalf of sovereign governments to private lenders, exchange rate regimes, and international bond contracts, highlight the evolution from commitment to flexibility. Early interaction with international markets typically benefits from strong transaction-specific commitment. However, the goal is to grow out of transactional commitments to achieve commitment through credible institutions. Institutional commitment allows the benefits of flexibility, with the country''s ""word"" acting as the necessary assurance to behave responsibly